Teori Reduksi Ketidakpastian dalam Cyber Romantic Relationship - Ketut Ajeng Sespiani; Monica Apilia; Irwansyah Irwansyah (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
The rapid development of technology and information in the digital era has an impact on the increasing use of social media which has brought significant changes to society. Social media has now been used by the community for various purposes, one of which is as a means of finding a partner or what we are familiar with as the phenomenon of online dating or cyber romantic relationships. The absence of a physical presence in cyber romantic relationships can lead to increased uncertainty. By using a qualitative descriptive approach method by collecting various previous studies, this writing was done to find out how the implementation of the uncertainty reduction theory of the cyber romantic relationship phenomenon in Indonesia. The results of this paper reveal that the relationships that exist in cyber romantic relationships tend to take place quickly from the introduction process to the commitment stage. Also, individuals communicate to reduce uncertainty. Passive and interactive strategy are always used in cyber romantic relationships.